Pemanfaatan jerami padi (Oryza sativa L.) sebagai bahan baku dalam pembuatan CMC (Carboximetil Cellulose) - Masrullita; Meriatna; Zulmiardi; Ferri Safriwardy; Auliani; Rizka Nurlaila (Jurnal Rekayasa Proses, 2021)
Rice straw is a waste from rice plants that contains 37.71% cellulose, 21.99% hemicellulose, and 16.62% lignin. High cellulose content in rice straw can be used as raw material for the manufacture of Carboxymethyl Cellulose (CMC). CMC is a cellulose derivative widely used in food, pharmaceutical, detergent, textile and cosmetic products industries as a thickener, stabilizer of emulsions, or suspensions and bonding. This study aims to process rice straw waste into CMC with variations in sodium monochloroacetate of 5,6,7,8 and 9 grams. The method used in this research is by synthesis using 15% NaOH solvent, with a reaction time of 3.5 hours and 5 grams of rice straw. The results showed that the best CMC was obtained at a concentration of 9 grams of sodium monochloroacete with a yield characterization of 94%, pH 6, water content of 13.39%, degree of substitution (Ds) of 0.80, and viscosity of 1.265 cP.